Molecular cloning of GA-suppressed G2 pea genes by cDNA RDA - 朱玉贤 张翼凤 李慧英 (Science China. Life sciences, 1997)
GA-treated and non-treated G2 pea cDNAs were compared using a newly developed method called cDNA representational difference analysis (cDNA-RDA), and several GA-suppressed mRNAs were found. After cloning of the larger fragments PGAS1-3 ( pea GA-suppressed cDNA 1-3), they were demonstrated to be expressed only in pea tissue not treated with GA3 through Northern analysis. Compared with subtractive hybridization and differ-ential display techniques, this method not only can be easily manipulated but also has a relatively low rate of false posi-tive and is highly repetitive. It is the major progress in molecular cloning techniques.